Brain tumors in Sweden: Data from a population-based registry 1999–2012. (March 2015) - Asklund, Thomas; Malmström, Annika; Bergqvist, Michael; Björ, Ove; Henriksson, Roger
Abstract: Background. The Swedish brain tumor registry has, since it was launched in 1999, provided significant amounts of data on histopathological diagnoses and on important aspects of surgical and medical management of these patients. The purpose is mainly quality control, but also as a resource for research. Methods. Three Swedish healthcare regions, constituting 40% of the Swedish population, have had an almost complete registration. The following parameters are registered: diagnosis according to SNOMED/WHO classification, symptoms, performance status, pre- and postoperative radiology, tumor size and localization, extent of surgery and occurrence of postoperative complications, postoperative treatment, such as radiotherapy and/or chemotherapy, other treatments, complications and toxicity, occurrence of reoperation/s, participation in clinical trials, multidisciplinary conferences and availability of a contact nurse. Results. Surgical radicality has been essentially constant, whereas the use of early (within 72 hours) postoperative CT and MRI has increased, especially for high-grade glioma, which is a reflection of quality of surgery. Survival of patients with high-grade glioma has increased, especially in the age group 60–69. Patients aged 18–39 years had a five-year survival of 40%. Waiting times for the pathological report has been slightly prolonged. Geographical differences do exist for some of the variables. Conclusion. Population-based registration is valuable for assessment of clinical management, which could have impact on patient care. As a result of short survival and/or the propensity to affect cognitive functions this patient group has considerable difficulties to make their voices heard in society. We therefore believe that a report like the present one can contribute to the spread of knowledge and increase the awareness for this patient group among caregivers and policy makers.